TRADISI SEWELASAN SEBAGAI SISTEM TA‘LIM - Suwito Suwito (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article describes the sewelasan culture as a learning system inAolia’ congregation Panggang, Yogyakarta. The data is collected by doinga depth interview and documentation. Sewelasan in Javanese traditionis used to empower the members. Character materials is exploredand elaborated from(sira>h) awliya>’ history which is read to trigger theconsciousness and closeness to God. The Islamic scholars transform thosevalues in analogy, symbols and dialogue among students.